WORKPLACE TOXICITY AND LEADERSHIP STRATEGIES - Teti Rohayati (LPSDI Bina Patria, 2022)
Workplace toxicity may negatively influence the well-being and work performance of employees. Best practices of successful leadership approaches and behaviors have been unidentified when addressing low-toxicity work environments. The purpose of this qualitative narrative case study was to develop a deeper understanding of how leaders selected and applied specific leadership strategies and behaviors in nontoxic workplace environments. Data were collected from 10 participants in New Hampshire using a purposive sampling technique and semistructured interviews based on Alvarado’s triangular model of workplace toxicity. This study was structured using a narrative approach to explore ways positive leaders practically implemented styles and behaviors to mitigate workplace toxicity. All participants met this study’s qualification parameters; they had past experiences with toxic leaders that shaped their personal leadership styles. NVivo was used to compare and analyze data from all interview transcripts entered for recurring themes. These themes were coded according to how answers connected to a specific research question, and findings were collated across interviews to form results. Three major themes emerged from the data: experience with toxic leadership, leadership approaches to toxicity, and leadership behaviors toward toxicity. Insights from this study may help company leaders avoid lawsuits, low productivity levels, and high staff turnover due to toxic workplace elements left unattended or ineffectively managed. The study may contribute to positive social change by generating practical models of and suggestions for creating a less toxic work environment, thereby creating healthier and happier employees, which increases public wellbeing and company success